Moral Value in Novel Tasawuf Love By M. HILMI AS'AD - Ramadania, Wulandari (Tarbiyah : Jurnal Ilmiah Kependidikan, 2017)
The moral value conveyed by the author to the reader through works of fiction especially novels is useful and useful to the reader. This study aims to describe the moral values associated with social messages and expose the moral values associated with the religious message contained in the novel Tasawuf Cinta by M. Hilmi As'ad. The method used in this research is analytic descriptive method. The results of this study indicate the moral values associated with social messages are: (1) social in social life; (2) relations between human beings of religion, and (3) association between the opposite sex. The moral values associated with the religious message are: (1) the relationship of man and God; (2) human nature and conscience; (3) the personal freedom that man possesses; And (4) the dignity and dignity of each individual.